Analisis motivasi berprestasi pada mahasiswa Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi - Wahyudi Firmansyah; Indra Jaya; Sumarni Sumarni (Jurnal Dinamika Manajemen, 2020)
This study aimed to look at the motivation of achievement in management students based on gender and length of study (force). This research is quantitative research by taking respondents from the 2014-2016 foster management study program. The number of samples used in the study was calculated using the Slovin formula to obtain a sample of 123 students. The data in questionnaires were analyzed using different tests, Kruskal Wallis and Mann Whitney. The results showed a difference between the motivation of student achievement judging by gender and length of study where gender will affect the motivation of accomplishment in students of the Management Study Program of the Faculty of Economics and Business, University of Jambi. At the same time, the old factor of study does not influence student achievement motivation